A construção temporal [XTEMP + (EM) + QUE + O] no português brasileiro - Moreira, Beatriz de Lucena (2016)
In this work, I investigate the temporal construction [XTEMP + (EM) + QUE + O], by considering its formal and functional aspects. I aim to analyze structural, semantic-cognitive and pragmatic aspects in its use. In terms of methodology, this paper is quantitative - being related to the construction description and its frequency, as well as qualitative - being related to its use motivation. In terms of corpus, this research uses historical written data from Projeto Para a História do Português Brasileiro (PHPB), and modern written and spoken texts from Corpus Discurso & Gramática. This work is based on Linguística Funcional Centrada no Uso (LFCU) theory, according to Bispo, Silva e Furtado da Cunha (2013). Furthermore, there are also Grammar Construction contributions, according to Goldberg (2006) and Traugott and Trousdale (2013). The results show, among other things, that the temporal construction license two subschematic patterns (different between each other due to preposition em presence or absence), which have semantic-syntactic and discursive-pragmatic specificities Also, the use of subschematic structures is related to the gender and linguistic modality in which they were produced and to invited inference. These subschemas occur together at least since 19th century and seem to be in competition, revealing constructional change. Besides, it looks like there is a constructionalization process inside the temporal construction investigated, involving smaller structures (in this case, [XTEMP], [(EM) QUE] and [O]), which become two new form-meaning pairings.